Effect of long-term nicorandil therapy on myocardial perfusion parameters according to triphosadenine stress-volume computed tomography in a patient with non-obstructive coronary artery disease: a care report - O. F. Egorkina; G. N. Soboleva; S. A. Gaman; Y. A. Karpov; S. K. Ternovoy (Столичная издательская компания, 2023)
A case of a patient with myocardial perfusion improvement according to volume computed tomography (VCT) of the heart with triphosadenine infusion against the background of optimal therapy, including nicorandil for 3,5 years, is presented. In a patient with an established diagnosis of non-obstructive coronary artery disease (CAD) in 2019, stress-induced myocardial ischemia of left ventricular (LV) septal and lateral area was detected. Repeated investigation 3,5 years later against the background of optimal therapy showed an ischemia decrease in the form of the disappearance of previously detected defects in the basal segments of the anteriorlateral and inferior-lateral walls and the middle segments of the anterior-septal and inferior-lateral walls of the LV.